Belanja Daerah, Dividen Penyertaan Modal, dan Dampaknya pada Produk Domestik Regional Bruto (PDRB) Kutai Timur - Syahrudi, Abdi Fauzan; Juhardi; Amalia, Siti (JOM, 2024)
This study aims to analyze the effect of Regional Expenditure and Dividends from Regional Government Capital Participation on Gross Regional Domestic Product (GRDP) and Fiscal Decentralization in East Kutai Regency using path analysis. The results showed that Regional Expenditure has a significant positive effect on GRDP, indicating that effective expenditure allocation can increase regional economic output. Dividends from Local Government Capital Participation have a positive but insignificant effect on GRDP, reflecting the fluctuating and smaller contribution of dividends compared to other income sources. Local Government Expenditure has a negative and insignificant effect on Fiscal Decentralization, due to high consumptive personnel expenditure. Dividends from Local Government Capital Participation also have a positive but insignificant effect on Fiscal Decentralization due to a decrease in the amount of capital participation. GRDP has a positive but insignificant effect on Fiscal Decentralization, influenced by taxes paid directly to the central government. However, Regional Expenditure has a positive effect on Fiscal Decentralization through GRDP, indicating that the efficiency of infrastructure spending increases Regional Original Revenue (PAD). Dividends from Local Government Capital Participation also have a positive effect on Fiscal Decentralization through GRDP, as it creates tax liabilities that increase PAD. This research implies that optimizing local expenditure and dividends can increase GRDP and the effectiveness of fiscal decentralization.